Impact of Social Protection Mechanism for Child Protection - Acharya, Debaki; Poudel, Tilottam; Khadka, Sumikshya; Tamrakar, Shristi; Tamrakar, Shreya (Journal of Social Protection, 2021)
Social protection schemes are designed to address the vulnerability of all the citizens through policy and programmes. As one of the integral agenda of the Government of Nepal, social protection programmes have covered a wide range of citizens through various schemes including cash, in-kind, and food transfers among others. Children, as the most vulnerable citizens needing support for growth, empowerment and sustenance, are the core recipients of the social protection programmes. Analysis of the current contribution of social protection programmes in child protection through the review of policy, programmes and budget allocated by the federal as well as provincial governments shows lack of compliance between the annual policy, programme and budget to shield children under social protection schemes. In addition, all the policy provisions haven’t been exclusively supported by budgetary provisions. Though significant benefits and social security allowances have been placed for children covering education, health, protection, nutrition, and development, this study shows further need of investment on children focused programmes. Similarly, it reveals that though Dalits, girls, conflict-affected, martyr’s children, children with disabilities and other most marginalised and disadvantaged are covered by the social protection programmes, a large part of the sexual and gender minority children have been excluded from these supports due to lack of awareness and accessibility to such schemes.